Naskah Utama Hasil Penelitian Analisis Faktor Kesulitan dalam Pembelajaran Bahasa Arab Siswa Kelas VIII SMP Miftahul Iman Kota Bandung - Lislis Cahyati; Tatang; Hikmah Maulani (MUMTAZA Journal of Arabic Teaching, Arabic Linguistic and Literature, 2023)
This study aims to analyze the factors of Difficulty in Learning Arabic for Class VIII Students of SMP Miftahul Iman Bandung City. This research is very important to be carried out to find out the various factors that are obstacles for grade VIII students of SMP Miftahul Iman Kota Bandung in learning Arabic and find solutions. This type of research is qualitative research. The research participants were class VIII students at SMP Miftahul Iman, Bandung City. Data collection methods and techniques are in the form of questionnaires distributed to grade VII students of SMP Miftahul Iman and interviews conducted by teachers who teach Arabic subjects. The results showed that the factors of difficulty learning Arabic for grade VIII students of SMP Miftahul Iman Kota Bandung include curriculum factors and their components, namely, learning objectives, materials, methods and learning media which if not good will affect the learning process of students. Furthermore, factors of lack of interest in learning Arabic, learning methods and media, students' perceptions of Arabic lessons, students' educational background, and bi'ah lughawiyyah, these factors greatly affect the learning process of grade VIII students of SMP Miftahul Iman Kota Bandung in Arabic lessons.